2021
DOI: 10.3390/su13179631
|View full text |Cite
|
Sign up to set email alerts
|

Science Mapping of the Global Knowledge Base on Management, Leadership, and Administration Related to COVID-19 for Promoting the Sustainability of Scientific Research

Abstract: The pandemic caused by the COVID-19 virus has resulted in inevitable radical changes across almost all areas of daily life, with the pandemic having revealed perhaps the greatest crisis humanity has faced in modern history. This study aims to provide thematic and methodological recommendations for future sustainable research programs through a bibliometric analysis of publications focused on management, leadership, and administration related to COVID-19. The data for the study were obtained from the Web of Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 86 publications
2
76
0
Order By: Relevance
“…Surveys on college students can be found in [19][20][21][22][23]. In [19], the authors studied 2739 students from China and Hong Kong and found that the COVID-19 pandemic had significantly reduced students' interest in studying abroad.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys on college students can be found in [19][20][21][22][23]. In [19], the authors studied 2739 students from China and Hong Kong and found that the COVID-19 pandemic had significantly reduced students' interest in studying abroad.…”
Section: Related Workmentioning
confidence: 99%
“…Most of them were older, concerned about the pandemic, and depressed. The latest works have been carried out by Turgut et al [22,23], who have focused on changes in educational processes due to COVID-19 for reducing the pandemic's negative effects and going forwards to a more effective working process.…”
Section: Related Workmentioning
confidence: 99%
“…Educators had to adapt to online teaching methods at all schooling levels and transform teaching materials for the new online space to ensure students could continue learning during the pandemic. In addition, both teachers and students had to learn how to use the various forms of online software used in distance education (Karakose et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there are still calls for more research focused on e-learning and b-blended modalities in higher education considering the expected growth for the coming years [1]. Scientific mapping on management and administration related to COVID-19 has shown that the trend of publications revolves around specific groups and the field of health, so making progress in other professional collectives can enrich scientific knowledge [2].…”
Section: Introductionmentioning
confidence: 99%
“…According to Maslach and Jackson [6] and Maslach et al [7], burnout as a syndrome has three dimensions: (1) emotional exhaustion that refers to feelings of being emotionally overextended and exhausted by one's work, (2) depersonalization that is a feeling of impersonal response toward students, and (3) a lack of personal accomplishment and a loss of personal self-efficacy. Job demands-resources is also a useful framework to explain the burnout dimensions.…”
Section: Introductionmentioning
confidence: 99%